2022
DOI: 10.1002/brb3.2705
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 administration produces crucial antidepressant‐like effects in a CUMS‐induced mice model of depression

Abstract: Introduction The most striking feature of depression is sadness and a loss of interest in activities, which represents a major cause of disability globally. Therefore, it is necessary to identify novel antidepressants for clinical practice. Ginsenoside Rh2 (Rh2) is one of the major bioactive ginsenosides that can be extracted from Panax ginseng and has been demonstrated to improve both memory and learning. The purpose of this study was to provide broad insight into the mechanisms underlying depression and gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…One study showed that when a Trk-B antagonist was injected into mice exposed to CUMS it completely blocked the BDNF/Trk-B signaling cascade. 46 Regarding the neurotrophic hypothesis of depression, reduced expression of BDNF and other growth factors may contribute to mood disorders, while upregulation of BDNF and its receptor Trk-B may be a key component of the action of all antidepressants. 47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that when a Trk-B antagonist was injected into mice exposed to CUMS it completely blocked the BDNF/Trk-B signaling cascade. 46 Regarding the neurotrophic hypothesis of depression, reduced expression of BDNF and other growth factors may contribute to mood disorders, while upregulation of BDNF and its receptor Trk-B may be a key component of the action of all antidepressants. 47…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that when a Trk-B antagonist was injected into mice exposed to CUMS it completely blocked the BDNF/Trk-B sig-naling cascade. 46 Regarding the neurotrophic hypothesis of depression, reduced expression of BDNF and other growth factors may contribute to mood disorders, while upregulation of BDNF and its receptor Trk-B may be a key component of the action of all antidepressants. 47 Our study found that BDNF levels were significantly lower in the serum and brain tissue of CUMS-induced depressed mice compared to controls ( p < 0.01); however, both BB and fluoxetine ameliorated these changes to some extent (Fig.…”
Section: Papermentioning
confidence: 99%
“…Recent studies found that antidepressants enhanced neurotrophy by activating the downstream PI3K/Akt pathway of TrkB 48,49 . Moreover, numerous studies have shown that chronic stress attenuated neurogenesis, which some antidepressants were relieved via activating TrkB 50,51 . Furthermore, previous evidence shown that antidepressants inhibited neuroinflammation by activating TrkB to reduce the levels of NF‐κB, NLRP3, and pro‐inflammatory factors 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…# p < 0.05 and ## p < 0.01 compared with the CUMS group. some antidepressants were relieved via activating TrkB 50,51. Furthermore, previous evidence shown that antidepressants inhibited neuroinflammation by activating TrkB to reduce the levels of NF-κB, NLRP3, and pro-inflammatory factors 52,53.…”
mentioning
confidence: 97%
“…134 Ginsenoside Rh2 and Rb1 exerts anti-depressant effects by positively regulating the BDNF-TrkB pathway. 135,136 Ginsenoside Rg1 increases the phosphorylation of BDNF, TrkB and Erk in the prefrontal cortex and improves learning, memory and adaptation by activating the BDNF/TrkB/Erk pathway in rats with CRS. 137 The mechanism by which ginsenosides improve PD is yet to be clarified.…”
Section: Ginsenoside May Activate the Bdnf/trkb Signaling Pathwaymentioning
confidence: 99%